Research on Visual Communication Design in the Perspective of Museum Display - Wu, Jiati (Transactions on Economics, Business and Management Research, 2023)
In the museum display, the unique way of visually conveying design information is based on cultural relic appraisal and exhibition appreciation, which has sufficient persuasiveness. As a medium for visually conveying design information in museums, it has distinct characteristics. The interaction between various visual media presented in museum design can mobilize the audience's various visual communication information presented in the design. Good visual communication design not only can better convey the visual communication design information from the perspective of museum display to the audience, clarify the distinct characteristics of visual communication design from the perspective of museum display, but also play a huge value and significance in the dissemination of visual communication design information in museum display. This article introduces the visual communication design elements in the traditional perspective of museum display. At meanwhile, simultaneously studies the visual communication design elements and their combination in the new museum presentation perspective under technological elements.